Development of reduced fat cream cheese by using inulin and WPC as a fat replacer - N, Krishna K; Ghosh, Bikash C (Indian Journal of Dairy Science, 2020)
Cream cheese is a soft, mild, rich, creamy white, slightly acidic, unripened cheese with diacetyl flavour. The focus of the present investigation was to develop reduced fat cream cheese by using inulin and WPC as a fat replacer. Cream Cheese (control) and Reduced Fat Cream Cheese (RFCC) were prepared by fermentation of cream and skim milk separately followed by straining with muslin cloth and hanging for 12-13hours at 7-8â°C. Fermented mass and fermented cream was then mixed in 3:1 and 6:1 ratio to obtain control and RFCC, respectively. Inulin and WPC of 4 and 6% were incorporated in RFCC. Cheese made with 4% inulin scored significantly (p